2020
DOI: 10.1016/j.simyco.2020.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting Metarhizium and the description of new species from Thailand

Abstract: Over the last two decades the molecular phylogeny and classification of Metarhizium has been widely studied. Despite these efforts to understand this enigmatic genus, the basal lineages in Metarhizium are still poorly resolved. In this study, a phylogenetic framework is reconstructed for the Clavicipitaceae focusing on Metarhizium through increased taxon-sampling using five genomic loci (SSU, LSU, tef, rpb1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
101
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(120 citation statements)
references
References 101 publications
3
101
0
1
Order By: Relevance
“…Many of these are rare locally distributed specialists. Thus, a 2020 paper [ 107 ] describes 19 new species with narrow host ranges in Thailand, seven of which produce a sexual morph.…”
Section: How Do Metarhizium Species Diversify Theimentioning
confidence: 99%
See 2 more Smart Citations
“…Many of these are rare locally distributed specialists. Thus, a 2020 paper [ 107 ] describes 19 new species with narrow host ranges in Thailand, seven of which produce a sexual morph.…”
Section: How Do Metarhizium Species Diversify Theimentioning
confidence: 99%
“…Thus, sex, or the lack thereof, plays an important role in pathogen strategies and the risks associated with genetic engineering. Molecular phylogenetic analyses of Metarhizium have shown that sexually reproductive Metarcordycep forms are distributed among clades comprised of Metarhizium isolates assumed to be reproducing asexually [ 28 , 29 , 107 ]. The requirements for sexual reproduction in the genus remain enigmatic, but observations suggest that sexual reproduction, as evidenced by teleomorphic forms (note that a teleomorph is the sexual stage of a fungus), is restricted to a narrow range of host insects in geographically restricted regions [ 107 , 208 ].…”
Section: Sexuality and Host Rangementioning
confidence: 99%
See 1 more Smart Citation
“…Sung et al (2007) revised it to O. jiangxiensis only based on the original morphological description. The species is closely similar to Metarhizium purpureonigrum, a recently-described species from Thailand (Mongkolsamrit et al 2020). Future studies are warranted to clarify its taxonomic placement.…”
Section: Ophiocordyceps Formosana (Kobayasimentioning
confidence: 56%
“…Notes. According to the description and pictures provided (Mongkolsamrit et al 2020), the species is probably a synonym of O. jiangxiensis, a traditional Chinese medicinal mushroom (Zha et al 2018, also see O. jiangxiensis below). Hosts of the species, which were recorded as Coleoptera larvae, are Elateridae larvae (Campsosternus sp.…”
Section: Metarhizium Purpureonigrum Luangsa-ard Tasanathai Thanakitmentioning
confidence: 99%